Market Based Approach in Clean Cooking Solutions in Kenya &Tanzania - Muok, Bernard (JOOUST, 2021)
The project aim at evaluating and developing strategies for catalysing the diffusion and adoption of clean cooking solutions in East Africa with focus in Kenta and Tanzania